Attenuated GLP-1 secretion in obesity: cause or consequence?. Issue 6 (June 1996) - Ranganath, L R; Beety, J M; Morgan, L M; Wright, J W; Howland, R; Marks, V
Abstract : BACKGROUND: Hypersecretion of insulinotropic factors such as glucose dependent insulinotropic polypeptide (GIP) and glucagon-like peptide-1(7-36)amide (GLP-1) have been postulated to account for the hyperinsulinaemia of obesity. AIMS: To examine the role of GLP-1 and GIP in obese women and matched controls. SUBJECTS: Six lean and six obese women subjects matched for age. METHODS: The gut hormone, plasma glucose, and serum triglyceride responses were studied over 180 minutes after oral carbohydrate and fat meals. Heparin (10, 000 units) was given intravenously at 120 minutes. RESULTS: There was pronounced attenuation of plasma GLP-1 secretion to oral carbohydrate in the obese compared with lean subjects but no such difference in response to oral fat load. There were no differences in the plasma GIP responses to carbohydrate or fat feeding. There was an apparent fall in plasma GLP-1 values in all subjects after administration of heparin. CONCLUSION: Postprandial GLP-1 secretion in response to oral carbohydrate is considerably attenuated in obese subjects. The cause of this attenuation of GLP-1 secretion is not known although we suggest that both this fall and the overall reduction in GLP-1 values in obese subjects may be related to an increase in plasma non-esterified fatty acids.